The dynamic linkages of Pakistani and global stock markets: Evidence from Karachi stock exchange - Sulaiman D. Mohammad; Adnan Hussain (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2011)
The aim of the study is to explore the long run association among Pakistani equity market and some developed and emerging equity markets. Weekly data from the period of 2000 to 2010 was applied in this study. The result highlighted Pakistani equity market well correlated with the American equity market. The impulse response function result also illustrated that the American equity market created more instability as compare to other equity markets of the world. The portfolio managers of UK, India, Germany and China have a great opportunity to diversify their portfolio to take comparatively greater advantage from KSE.
Keywords: 330; Portfolio diversification; Equity Market; Karachi Stock Exchange; Portfolio-Management; Spekulation; Börsenkurs; Spillover-Effekt; Pakistan; Welt